Reactivity of heterophospholes toward 1,3-dipolar cycloaddition of diazo compounds - An FMO analysis - Schatz, Jürgen; et al. (Journal of Physical Organic Chemistry, 2003)
The molecular geometries and the frontier orbital energies of three diazo compounds [diazodiphenylmethane (2), the α-silyl-α-diazoketone 3 and the isomeric 2-siloxy-1-diazoalkene 4], 10 heterophospholes with a P=C bond and two heterophospholes with a P=N bond were obtained from DFT calculations at the B3LYP/6-311+G** level. The 1,3-dipolar cycloaddition reactivity of diazo compounds 2-4 toward the heterophospholes is discussed on the basis of FMO theory. It is concluded that in most cases, the dominant frontier orbital interaction is between the HOMO(diazo) and the LUMO(heterophosphole), and that the reactivity should decrease in the order 2 >4 >3. The 1, 2-thiaphosphole 9 and 1,3-azaphosphole 10 have HOMOs of high energy and, therefore, the HOMO(heterophosphole)-LUMO(diazo) interaction is also important. Among the different types of heterophospholes considered here, the 2-acyl-1,2,3-diazaphosphole 5, 3H-1,2,3,4-triazaphosphole 8, 1,2-thiaphosphole 9 and 1,3,4-thiazaphosphole 14 are predicted to have the highest dipolarophilic reactivities. These conclusions are in qualitative agreement with available experimental results. Copyright © 2003 John Wiley & Sons, Ltd.